Antinociceptive activity, elucidation of mechanism of action and identification of bioactive components of muntingia calabura L. Leaf extracts - Mohd Sani, Mohd Hijaz (2016)
Research into plant as an alternative treatment for pain has been widely explored due to its potentially low adverse effect with great therapeutic activity. Muntingia calabura L. (Tiliaceae) has recently gained a medicinal status as well as attention from throughout the world. The present study examined the potential antinociceptive activity of methanol extract of Muntingia calabura (MEMC) leaves using the acetic acid-induced abdominal constriction, formalin and hot plate test following the determination of its safety using acute toxicity test. Then the possible involvement of MEMC-induced antinociception through capsaicin, glutamate, bradykinin, opioidergic, dopaminergic serotonergic, noradrenergic, adenosisnergic, protein kinase C (PKC), nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) and potassium channel pathway was evaluated. Experimental animals (n=6) were pretreated orally with 10% dimethyl sulfoxide (DMSO; negative control), 5 mg/kg morphine or 100 mg/kg aspirin (positive control) or 100, 250, and 500 mg/kg of MEMC, followed by the administration of receptor antagonists and/or induction of nociception. The crude MEMC extract was further partitioned into three fractions: petroleum ether extract (PEMC), ethyl acetate extract (EAMC) and aqueous extract (AEMC). The antinociceptive profiling demonstrates PEMC produced a significantly better activity than EAMC and AEMC. Possible mechanism of PEMC action was studied using the same assays. Result on the acute toxicity study shows no mortality and significant behavioural and physiological changes detected. Oral administration of MEMC and PEMC shows a dose-dependent inhibition in acetic acid-induced abdominal constriction test, formalin-, capsaicin-. glutamate-, bradykinin- and PMA-induced paw licking test, while only the highest dose produced significant pain inhibition in hot plate test. Furthermore, the antinociception caused by MEMC and PEMC in acetic acid-induced abdominal constriction test was significantly attenuated by intraperitoneal treatment of naloxone (non-specific opioid receptor antagonist; 5 mg/kg), naltrindole (δ opioid receptor antagonist; 1 mg/kg) norbinaltorphimine (κ opioid receptor antagonist; 1 mg/kg), β-funaltraxamine (μ opioid antagonist; 10 mg/kg), pindolol (5-HT1A receptor antagonist; 1 mg/kg), caffeine (nonselective adenosine receptor antagonist; 3 mg/kg) and yohimbine (α2 adrenoceptor antagonist; 0.15 mg/kg). While both extracts did not act on dopaminergic receptor system, PEMC, but not MEMC, was significantly reversed by i.p. injection of atropine (non-selective cholinergic antagonist; 10 mg/kg). At the same time, MEMC and PEMC were found to inhibit pain through NO/cGMP/PKC as well as potassium channel pathways. The potential antinociceptive activity seen was probably due to synergistic effect of flavonoids, tannins, polyphenolic compounds, triterpene and steroid present in the extracts based on their phytochemical screening. High performance liquid chromatography analysis shows several peaks, detected at different wavelengths of the chromatogram, which were suggested to be flavonoid-based compounds. In conclusion, the synergistic effects of various bioactive components suggested to be responsible in the antinociceptive activity of MEMC as well as the semi-purified PEMC extract which involved in central and peripheral pain pathways. The activation of potassium pathway as well as opioid, adenosinergic, noradrenergic and serotonergic receptors while inhibits NO/cGMP/PKC pathways, TRPV1, glutamate and bradykinin receptors might be the possible mode of action of both the extracts in exerting their analgesic effect.